The prognostic role and metabolic function of GGPS1 in oral squamous cell carcinoma - Huang, Ke; Han, Liang; Xu, Huimei; Xu, Ruiming; Guo, Hao; Wang, Huihui; Xu, Zhaoqing (Frontiers in Molecular Biosciences, 2023)
GGPS1(geranylgeranyl diphosphate synthase 1) is a member of the prenyltransferase family. Abnormal expression of GGPS1 can disrupt the balance between protein farnesylation and geranylgeranylation, thereby affecting a variety of cellular physiologic and pathological processes. However, it is still unknown how this gene could contribute to the prognosis of oral squamous cell carcinoma (OSCC). This study aimed to explore the prognostic role of GGPS1 in OSCC and its relationship with clinical features. The RNA-seq data and clinical data were obtained from TCGA. The survival analyses, Cox regression analyses, ROC curves, nomograms, calibration curves, and gene function enrichments were established by R software. The results showed that the high expression of GGPS1 in OSCC is related to poor prognosis. At the same time, multivariate Cox regression analyses showed that GGPS1 could be an independent prognostic biomarker, and its gene expression level is closely related to the histological stage of cancer. GGPS1 may promote tumorigenesis because of its metabolic function. This study came to a conclusion that GGPS1, whose high expression has a significantly unfavorable meaning toward the prognosis of OSCC, can act as a novel independent biomarker for OSCC.